2015
DOI: 10.1007/s10711-015-0057-9
|View full text |Cite
|
Sign up to set email alerts
|

The hyperplane is the only stable, smooth solution to the Isoperimetric Problem in Gaussian space

Abstract: Abstract. We study stable, two-sided, smooth, properly immersed solutions to the Gaussian Isoperimetric Problem. That is, we study hyper-surfaces Σ n ⊂ R n+1 that are second order stable critical points of minimizing Aµ(Σ) = Σ e −|x| 2 /4 dA for compact variations that preserve weighted volume. Suchshow that such Σ satisfy the curvature condition H = x, N /2 + C where C is a constant. We also derive the Jacobi operator L for the second variation of such Σ. Our first main result is that for non-planar Σ, bounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 17 publications
4
68
0
Order By: Relevance
“…In [2] and [3], Barbosa-do Carmo-Eschenburg showed that a constant mean curvature (CMC) hypersurface in a Riemannian manifold is the critical point of its area functional for compactly supported variations which preserve enclosed volume. Mcgonagle-Ross [24] proved the same property for CWMC hypersurfaces in R m under the Gaussian weighted area and Gaussian weighted volume, respectively. Using the similar argument to the one in [3] and [24], one can show that a CWMC hypersurface in a Riemannian manifold is still the critical point of its weighted area functional for compactly supported variations which preserve enclosed weighted volume, where the weighted volume element in M is e −f dv M and dv M denotes the volume element of M .…”
Section: Preliminariesmentioning
confidence: 70%
See 2 more Smart Citations
“…In [2] and [3], Barbosa-do Carmo-Eschenburg showed that a constant mean curvature (CMC) hypersurface in a Riemannian manifold is the critical point of its area functional for compactly supported variations which preserve enclosed volume. Mcgonagle-Ross [24] proved the same property for CWMC hypersurfaces in R m under the Gaussian weighted area and Gaussian weighted volume, respectively. Using the similar argument to the one in [3] and [24], one can show that a CWMC hypersurface in a Riemannian manifold is still the critical point of its weighted area functional for compactly supported variations which preserve enclosed weighted volume, where the weighted volume element in M is e −f dv M and dv M denotes the volume element of M .…”
Section: Preliminariesmentioning
confidence: 70%
“…So an f -minimal hypersurface Σ is the case of C = 0, that is, H = ∇f, n . When (M, g) is the Euclidean space (R m , g 0 ) with the Gaussian measure e − |x| 2 4 dv g 0 , a CWMC hypersurface is just the solution to the Gaussian isoperimetric problem in [24] or the λ-hypersurface in [6] (observe that in [6], the weighted measure is taken to be e − |x| 2 2 dv g 0 , which has no essential difference).…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Problem: Naturally we believe and expect that the additional condition (1.4) in Theorem 7.1 could be dropped; Furthermore, motivated by the main theorem of [27], it is also expected, without any additional conditions, that the m-planes are the only properly immersed, complete W -stable ξ-submanilds or, if it is not the case, more examples could be found. Remark 1.1.…”
Section: Consequently the Following Problem Is Interestingmentioning
confidence: 99%
“…More generally, we consider the rigidity of λ-hypersurfaces. The concept of λhypersurfaces was introduced independently by Cheng-Wei [7] via the weighted volume-preserving mean curvature flow and McGonagle-Ross [25] via isoperimetric type problem in a Gaussian weighted Euclidean space. Precisely, the hypersurfaces of Euclidean space satisfying the following equation are called λ-hypersurfaces:…”
Section: Introductionmentioning
confidence: 99%